True, true, unrelated? A review of recent evidence for a causal influence of breakfast on obesity. Issue 5 (October 2016) - Dhurandhar, Emily J.
Abstract : Purpose of review: It has long been known that breakfast skipping is associated with obesity; however, well controlled clinical trials have only recently been conducted to determine a causative relationship. Recent findings: Skipping breakfast is likely to be detrimental for insulin sensitivity; however, randomized trials suggest that it does not play a large role in weight gain or weight loss. Specific breakfast strategies such as certain types of breakfast, and consuming more calories in the morning relative to the evening, however, may produce greater weight loss. Summary: The act of eating breakfast, compared to skipping it, does not appear to have a large impact on body weight. More specific strategies regarding the size and type of breakfast may be required for a substantial effect on weight loss, and improving glycemic regulation may be an important reason to consume breakfast rather than skipping it.